A composite ZTA substrate and its preparation method and application
By setting the composite surface layer and high-temperature sintering on the ZTA substrate to form residual compressive stress, the problems of complex preparation process and poor product uniformity are solved, and the high thermal conductivity and good bending strength of the composite ZTA substrate are achieved.
Patent Information
- Application Number
- CN202310895847.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The existing ZTA substrates are complex in operation during the preparation process, and the uniformity of the finished product is difficult to control, resulting in uneven thermal conductivity and bending strength.
A composite surface layer is provided on the ZTA substrate, and ZTA is coated with aluminum oxide to form a composite network structure to improve thermal conductivity and bonding strength, and residual compressive stress of the surface layer is formed through high-temperature sintering to increase the bending strength.
The thermal conductivity and bending strength of the composite ZTA substrate are synchronously improved, the preparation process is simple and easy to operate, and the uniformity of the finished product is guaranteed.
Smart Images

Figure BDA0004352911390000121 
Figure BDA0004352911390000131 
Figure BDA0004352911390000132
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a composite ZTA substrate and a preparation method and application thereof. Background Art
[0002] With the vigorous development of the microelectronics packaging industry, electronic packaging technology is developing towards miniaturization, high density, multi-power and high reliability, and electronic packaging materials play an important role in the packaging field. Common substrate materials are mainly divided into four categories: plastic substrates, metal substrates, ceramic substrates and composite substrates. Zirconia toughened alumina ceramic (ZTA) substrates are superior to ordinary glass fiber PCB boards in terms of heat dissipation performance, current carrying capacity, insulation, thermal expansion coefficient, etc., and are therefore widely used in high-power power electronic modules, aerospace, military electronics and other products.
[0003] During the use of the substrate, the electronic components need to be supported and protected, and the heat generated by the circuit operation will generate certain thermal stress during the heat release and cooling process, so that the substrate material needs to have a certain bending strength and thermal conductivity, so that the service life of the entire circuit board will not be shortened due to the existence of thermal stress during use, thereby ensuring the reliability and stability of the electronic components. The existing technology improves the thermal conductivity and bending strength of the alumina substrate by static pressing or plating an alumina coating on the ZTA substrate, but there are the following problems: (1) The preparation process is relatively complicated: it is necessary to cast alumina green billets, transition layers, etc., and due to the large difference between the two green billets, the debinding curve and the sintering curve are difficult to explore, and it is easy to produce cracks during the sintering process, and the connection of the sintered substrate is not tight enough; (2) The uniformity of the finished product is difficult to control: due to the different sintering pressure and sintering position, the transition structure set between the layers is difficult to ensure consistency, so that the thickness of the transition layer obtained by each sintering is inconsistent, and it is difficult to ensure the uniformity of the thermal conductivity and bending strength of each piece after the porcelain is formed.
[0004] Therefore, there is an urgent need to provide a composite ZTA substrate, which has good thermal conductivity and bending strength, and a simple preparation process and is easy to operate. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions. The present invention provides a composite ZTA substrate, which has good thermal conductivity and bending strength, and has a simple preparation process and is easy to operate.
[0006] The inventive concept of the present invention is as follows: the present invention arranges a composite material surface layer on the ZTA substrate, the composite material surface layer is a composite network structure formed by alumina coating ZTA, the thermal conductivity of the composite material surface layer is higher than the thermal conductivity of the ZTA substrate, and the thermal conductivity of the composite ZTA substrate can be improved. At the same time, both the ZTA substrate and the composite material surface layer contain ZTA. When the ZTA substrate and the composite material surface layer are combined, due to the presence of the same component ZTA, the interlayer bonding and transition are tighter, so that the composite ZTA substrate has good bonding strength, and the improvement of bonding strength helps to improve the thermal conductivity and other properties of the composite ZTA substrate. In addition, ceramic materials are typical brittle materials, and the surface residual compressive stress can greatly improve the overall bending strength. The expansion coefficient of the composite material surface layer is lower than the expansion coefficient of the ZTA substrate. After the composite material surface layer is sprayed on the surface of the ZTA substrate green body, it is sintered at high temperature, and the surface residual compressive stress is formed due to the different shrinkage, which can improve the bending strength of the ZTA substrate, so that the bending strength and thermal conductivity of the composite ZTA substrate are improved at the same time, realizing the integrated design of structure and function.
[0007] Therefore, a first aspect of the present invention provides a composite ZTA substrate.
[0008] Specifically, a composite ZTA substrate comprises a ZTA substrate and a composite material surface layer located on the ZTA substrate; the composite material surface layer comprises aluminum oxide and ZTA; and the aluminum oxide is coated around the ZTA to form a wrapping structure;
[0009] The ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate is 1:(20-500);
[0010] In the surface layer of the composite material, the mass percentage of the aluminum oxide is 75-88%, and the mass percentage of the ZTA is 12-25%.
[0011] Specifically, the ZTA substrate is prepared from ZTA powder, and both the ZTA substrate and the surface layer of the composite material contain ZTA. When the ZTA substrate and the surface layer of the composite material are combined, due to the presence of the same component ZTA, the interlayer bonding and transition are tighter, so that the composite ZTA substrate has good bonding strength, and the improvement of bonding strength helps to further improve the thermal conductivity and other properties of the composite ZTA substrate.
[0012] Preferably, the ratio of the thickness of the composite material surface layer to the thickness of the ZTA substrate is 1:(300-500).
[0013] Specifically, when the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate is less than 1:500, the thickness of the ZTA substrate is too thick, the thickness of the surface layer of the composite material is too thin, the content of the composite material accounts for a relatively low proportion of the overall content of the composite ZTA substrate, and the thermal conductivity of the composite ZTA substrate obtained after sintering is low. When the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate is greater than 1:20, the relative thickness of the ZTA substrate is too thin, and the surface residual compressive stress formed by shrinkage after high-temperature sintering is small, which is insufficient to improve the bending strength performance of the ZTA substrate, resulting in poor bending strength of the composite ZTA substrate.
[0014] Preferably, in the surface layer of the composite material, the mass percentage of the aluminum oxide is 80-85%, and the mass percentage of the ZTA is 15-20%.
[0015] Preferably, in the surface layer of the composite material, the XRD diffraction peak intensity of the aluminum oxide
[006] plane is 10-45% of the XRD diffraction peak intensity of the aluminum oxide
[110] plane.
[0016] Specifically, the thermal shock resistance of ZTA substrate and the I 006 / I 110 There is a positive correlation, when the I of aluminum oxide 006 / I 110 When the ratio is lower than 10%, the crystals grow in a directional manner during the sintering process of the ZTA substrate, the arrangement structure is tight, and the thermal expansion coefficient is high, resulting in poor thermal shock resistance. If the ratio is higher than 45%, the atomic arrangement of the
[006] crystal plane and the
[110] crystal plane in the alumina crystal is different, the growth is anisotropic, resulting in different surface driving energy, large differences in the growing grain boundaries, and poor strength and thermal conductivity of the substrate after sintering.
[0017] Preferably, the raw materials for preparing the ZTA include alumina powder, zirconium oxide powder and a sintering aid.
[0018] Preferably, the mass percentage of the aluminum oxide powder is 91.2-95.8%, the mass percentage of the zirconium oxide powder is 0.2-4.8%, and the rest is sintering aid.
[0019] Further preferably, the mass percentage of the aluminum oxide powder is 92.0-95.0%, the mass percentage of the zirconium oxide powder is 1.0-4.0%, and the rest is sintering aid.
[0020] Preferably, the sintering aid includes at least one of Y2O3, MgO, CaO, SiO2, TiO2, CeO2, Cr2O3, La2O5, BaO, SrO, Sc2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3 and Ho2O3.
[0021] The second aspect of the present invention provides a method for preparing the composite ZTA substrate according to the first aspect of the present invention, comprising the following steps:
[0022] (1) mixing alumina powder, zirconium oxide powder and a sintering aid, crushing and granulating to obtain ZTA powder;
[0023] (2) mixing the ZTA powder obtained in step (1) with an organic solvent and a first auxiliary agent, performing tape casting, drying, and pre-sintering to remove binder to obtain a ZTA substrate green body;
[0024] (3) mixing the ZTA powder obtained in step (1) with water, a second auxiliary agent, and alumina powder to obtain a suspension;
[0025] (4) spraying the suspension obtained in step (3) onto the ZTA substrate green body obtained in step (2), and drying to obtain a composite ZTA substrate green body;
[0026] (5) Sintering the composite ZTA substrate green body obtained in step (4) to obtain a composite ZTA substrate.
[0027] Preferably, in step (1), the particle size of the ZTA powder is 3-8 μm.
[0028] Preferably, in step (2), the organic solvent comprises at least one of butyl acetate, ethyl acetate and anhydrous ethanol.
[0029] Preferably, the mass of the organic solvent is 2.7-3.8 times the mass of the ZTA powder added in step (2); further preferably, the mass of the organic solvent is 3-3.5 times the mass of the ZTA powder added in step (2).
[0030] Preferably, in step (2), the first auxiliary agent includes a dispersant, a binder, a plasticizer and a defoaming agent.
[0031] Preferably, the dispersant includes at least one of triolein, polyvinyl ester, polyethylene, polyacrylamide, aminopropyltrimethoxysilane, and polyoxyethylene alkylphenol ether.
[0032] Preferably, the mass of the dispersant is 0.18-0.55% of the mass of the ZTA powder added in step (2); further preferably, the mass of the dispersant is 0.2-0.5% of the mass of the ZTA powder added in step (2).
[0033] Preferably, the binder includes at least one of polyvinyl butyral, acrylate and polyvinyl alcohol.
[0034] Preferably, the mass of the binder is 9-13% of the mass of the ZTA powder added in step (2); further preferably, the mass of the binder is 10-12% of the mass of the ZTA powder added in step (2).
[0035] Preferably, the plasticizer includes at least one of dibutyl phthalate, dibenzyl phthalate and glycerol.
[0036] Preferably, the mass of the plasticizer is 0.01-0.06% of the mass of the ZTA powder added in step (2); further preferably, the mass of the plasticizer is 0.02-0.05% of the mass of the ZTA powder added in step (2).
[0037] Preferably, the defoaming agent includes at least one of polyacrylamide, sodium polyacrylate, and styrene-maleic anhydride copolymer.
[0038] Preferably, the mass of the defoaming agent is 0.01-0.06% of the mass of the ZTA powder added in step (2); further preferably, the mass of the defoaming agent is 0.02-0.05% of the mass of the ZTA powder added in step (2).
[0039] Preferably, in step (2), the thickness of the ZTA substrate green body is 0.25-1.5 mm.
[0040] Specifically, the thickness of the ZTA substrate green body includes but is not limited to the casting thickness, which can be adjusted according to different models and sizes.
[0041] Preferably, in step (2), the temperature of the pre-sintering and binder removal is 500-700° C., and the insulation time of the pre-sintering and binder removal is 20-50 min.
[0042] Further preferably, in step (2), the temperature of the pre-sintering and debinding is 550-650° C., and the insulation time of the pre-sintering and debinding is 30-40 min.
[0043] Preferably, step (3) is specifically as follows: firstly, the ZTA powder obtained in step (1) is mixed with water, and stirred, then the second auxiliary agent is added and mixed, and stirring is continued, and finally, alumina powder is added and stirred continuously to obtain a suspension.
[0044] Preferably, in step (3), the ratio of the particle size of the ZTA powder to the particle size of the alumina powder is (0.6-1.6):(0.03-0.1).
[0045] Further preferably, in step (3), the particle size of the ZTA powder is 3-8 μm, and the particle size of the alumina powder is 0.15-0.5 μm.
[0046] Specifically, the particle size of ZTA powder: alumina powder is in the range of (0.6-1.6): (0.03-0.1). The particle size of alumina powder needs to be smaller than that of ZTA powder to satisfy the coating relationship between the two. If the particle size ratio range of ZTA and Al2O3 is too narrow, the gaps between the powders cannot be filled by small particles during casting, resulting in more pores after sintering, which will enhance the scattering of phonons, increase the free path of phonon propagation, and reduce the thermal conductivity of the material. If the particle size distribution range is wide, it will lead to the accumulation of local particles of the material and produce differences in densification, which will cause the pore structure to become larger and affect the strength and thermal conductivity.
[0047] When the particle size of ZTA powder is less than 3μm, it is not much different from the particle size of alumina powder, and cannot carry its coating well, resulting in low bonding strength and bending strength after sintering; when the particle size of ZTA powder is greater than 8μm, the particle size of ZTA powder is too large, resulting in low porcelain strength after sintering, and when the particle size is too large, the sintering activity of the substrate is low, requiring a higher sintering temperature.
[0048] When the particle size of alumina powder is less than 0.15μm, the electrostatic force between powders is strong, and powders are easy to agglomerate. The finer the powder, the more grain boundaries are formed, which will enhance the intensity of phonon scattering by grain boundaries, resulting in reduced thermal conductivity of the material. When the particle size of alumina powder is greater than 0.5μm, the difference between it and the particle size of ZTA powder is small. After sintering, it cannot be well coated on the surface of ZTA powder, and the formed composite network structure is missing, resulting in reduced bonding strength and bending strength.
[0049] Preferably, in step (3), the water is deionized water.
[0050] Preferably, the mass ratio of the ZTA powder to the water is 1:(4.0-6.0); further preferably, the mass ratio of the ZTA powder to the water is 1:5.
[0051] Preferably, in step (3), the stirring time is 11-15 h; further preferably, the stirring time is 12-14 h.
[0052] Preferably, in step (3), the second auxiliary agent includes a dispersant and a defoaming agent.
[0053] Preferably, the dispersant includes at least one of triolein, polyvinyl ester, polyethylene, polyacrylamide, aminopropyltrimethoxysilane, and polyoxyethylene alkylphenol ether.
[0054] Preferably, the added amount of the dispersant is 0.5-3wt%; further preferably, the added amount of the dispersant is 1-2wt%.
[0055] Preferably, the defoaming agent includes at least one of polyacrylamide, sodium polyacrylate, and styrene-maleic anhydride copolymer.
[0056] Preferably, the amount of the defoamer added is 0.05-0.3 wt %; further preferably, the amount of the defoamer added is 0.1-0.2 wt %.
[0057] Preferably, the stirring is continued for 20-30 hours; more preferably, the stirring is continued for 24-26 hours.
[0058] Specifically, after continuing to stir, a suspension in which the dispersant is coated on the surface of the ZTA powder is obtained.
[0059] Preferably, after adding the alumina powder, stirring is continued to obtain a suspension, and the continuous stirring time is 8-12 hours.
[0060] Specifically, alumina powder is added and stirred continuously to obtain a suspension of alumina powder coated with ZTA powder, and the dispersant acts on the surfaces of the alumina powder and the ZTA powder to prevent agglomeration of the powders after mixing, thereby obtaining a uniform coating structure.
[0061] Preferably, based on the total mass of the suspension obtained in step (3) being 100 wt%, in the suspension, the mass fraction of the alumina powder is 75-88%, and the mass fraction of the ZTA powder is 12-25%.
[0062] Further preferably, in the suspension, the mass fraction of alumina powder is 80-85%, and the mass fraction of ZTA powder is 15-20%.
[0063] Specifically, the mass fractions of alumina powder and ZTA powder in the suspension obtained in step (3) are the same as the mass fractions of alumina and ZTA in the surface layer of the composite material of the composite ZTA substrate finally prepared.
[0064] Specifically, in ZTA powder, due to the presence of zirconium oxide powder, the thermal expansion coefficient of ZTA is greater than that of alumina powder, and the sintering temperature of ZTA powder is lower than that of alumina powder, so when the grains are sintered, they are still in a high-temperature stress state, which is conducive to the martensitic phase transformation from tetragonal phase to monoclinic phase. The shear stress and volume expansion of the phase transformation grains produce pressure strain on the ZTA substrate, so that crack expansion requires more energy. The content of ZTA powder is controlled to be not less than 12wt%, thereby increasing the toughness of the ZTA substrate. However, under high-temperature working environment, zirconium oxide is not only a toughening phase in ZTA ceramics, but also a conductive phase. When the content of ZTA powder exceeds a certain amount (greater than 25wt%), ZTA ceramic copper-clad circuit boards will have leakage current, and heating components will break down when used, causing product failure. Therefore, the amount of ZTA powder should be appropriate to obtain a composite ZTA substrate with high hardness, wear resistance, good fracture toughness and high bending strength.
[0065] Preferably, in step (4), the drying temperature is 85-130°C; further preferably, the drying temperature is 90-120°C.
[0066] Preferably, in step (4), the obtained composite ZTA substrate green body comprises a ZTA substrate green body and a composite material surface layer located on the ZTA substrate green body.
[0067] Preferably, the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate green body is 1:(20-500); further preferably, the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate green body is 1:(300-500).
[0068] Specifically, the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate green body is the same as the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate in the composite ZTA substrate after final sintering.
[0069] Preferably, in step (5), the sintering temperature is 1200-1500° C.; and the sintering holding time is 20-70 min.
[0070] Further preferably, the sintering temperature is 1300-1450° C.; and the sintering holding time is 30-60 min.
[0071] Specifically, when the suspension is sprayed on the ZTA substrate green body and sintered, the dispersant will be discharged together with the remaining organic components, and the surface layer of the composite material is a continuous network structure of alumina powder, isolating the ZTA powder. In this network structure, the ZTA powder can be better combined with the prepared ZTA substrate, and the surface layer of the composite material with better thermal conductivity is continuously phonon-conducted, so that the prepared composite ZTA substrate has better thermal conductivity.
[0072] A third aspect of the present invention provides an electronic product.
[0073] Specifically, the electronic product includes the composite ZTA substrate described in the first aspect of the present invention.
[0074] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0075] (1) The present invention provides a composite material surface layer with a composite network structure formed by coating ZTA powder with alumina powder on a ZTA substrate. The thermal conductivity of the composite material surface layer is higher than that of the ZTA substrate, thereby improving the thermal conductivity of the composite ZTA substrate. In addition, by utilizing the surface residual compressive stress of the ceramic material, after spraying the composite material surface layer on the surface of the ZTA substrate green body and sintering, residual compressive stress on the surface is formed due to the difference in shrinkage, thereby improving the bending strength of the ZTA substrate. This improves both the bending strength and the thermal conductivity of the composite ZTA substrate, thereby realizing a structural and functional integrated design.
[0076] (2) In the preparation process, the present invention controls key parameters such as material composition and content, thickness ratio of the ZTA substrate and the composite material surface layer, so that the thermal conductivity and bending strength of the substrate are improved simultaneously.
[0077] (3) Since the ZTA substrate and the surface layer of the composite material of the present invention both contain the same component ZTA, the interlayer bonding and transition are tighter, and a transition layer structure (such as Figure 1 As shown), the composite ZTA substrate has good bonding strength, and the improvement of bonding strength helps to further improve the thermal conductivity and other properties of the composite ZTA substrate.
[0078] (4) The preparation process of the present invention is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is the microstructure diagram of the transition layer of the present invention. DETAILED DESCRIPTION
[0080] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0081] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0082] Example 1
[0083] A composite ZTA substrate comprises a ZTA substrate and a composite material surface layer located on the ZTA substrate; the composite material surface layer comprises aluminum oxide and ZTA; and the aluminum oxide is coated around the ZTA to form a wrapping structure.
[0084] A method for preparing a composite ZTA substrate comprises the following steps:
[0085] (1) Weigh 92.0% alumina powder and 4.0% zirconia powder by mass, add 4.0% sintering aid (Y2O3, MgO, CaO mixed in equal proportions), use a ball mill to fully mix, and then crush and granulate to obtain ZTA powder with a particle size of 7 μm;
[0086] (2) Weigh the ZTA powder obtained in step (1), add an organic solvent (3 times the mass of the ZTA powder added in step (2), ethyl acetate and anhydrous ethanol mixed in equal proportions), a dispersant triolein (0.3% of the mass of the ZTA powder added in step (2)), a binder polyvinyl butyral (10% of the mass of the ZTA powder added in step (2)), a plasticizer dibutyl phthalate (0.02% of the mass of the ZTA powder added in step (2)), and a defoamer sodium polyacrylate (0.02% of the mass of the ZTA powder added in step (2)) according to a certain proportion, stir and mix them thoroughly to form a slurry, and prepare a ZTA green body with a thickness of 0.86 mm by a tape casting process, dry the ZTA green body, and then heat it at a high temperature of 600° C. for 30 minutes to complete pre-sintering and debinding, and ensure flatness to obtain a ZTA substrate green body;
[0087] (3) Weigh 80 wt% of alumina powder and 20 wt% of ZTA powder obtained in step (1), wherein the particle size of the alumina powder is 0.2 μm; uniformly disperse the ZTA powder in a deionized water solution by stirring (the mass ratio of ZTA powder to deionized water is 2:10), add 200 wt% (based on the mass of the alumina powder and the ZTA powder added in step (3)) of ceramic grinding balls, and stir at a speed of 100 rpm for 12 h to obtain a ZTA suspension; add 1 wt% (based on the mass of the alumina powder and the ZTA powder added in step (3)) of ammonium polyacrylate dispersant and 0.1 wt% (based on the mass of the alumina powder and the ZTA powder added in step (3)) of sodium polyacrylate defoamer to the ZTA suspension, and continue stirring for 24 h; add alumina powder to the above ZTA suspension, and continue stirring for 10 h to obtain a suspension of alumina powder coated with ZTA powder;
[0088] (4) spraying the suspension obtained in step (3) uniformly on the ZTA substrate green body obtained in step (2) by a spraying process, so that the suspension uniformly wraps the surface of the ZTA substrate green body and forms a composite material surface layer on the surface, and then drying the whole at 100° C. to obtain a composite ZTA substrate green body; the ratio of the thickness of the composite material surface layer to the ZTA substrate green body is 1:300;
[0089] (5) The composite ZTA substrate green body obtained in step (4) is sintered at a high temperature of 1350° C. for 30 min, and then cooled to obtain a composite ZTA substrate.
[0090] The microstructure of the transition layer structure formed after the suspension of Example 1 of the present invention is sprayed on the ZTA substrate green body and sintered is as follows: Figure 1 As shown, Figure 1 (a) is the interlayer SEM image of the ZTA substrate and the composite surface layer. Figure 1 (a) The left area is the ZTA substrate, the right area is the composite surface layer, and the box is the transition layer structure; Figure 1 (b) Figure 1 (a) Enlarged view of the transition layer in the box.
[0091] Example 2
[0092] The only difference between Example 2 and Example 1 is that in step (1) of the preparation method, the mass fraction of the aluminum oxide powder is 91.2%, and the mass fraction of the zirconium oxide powder is 4.8%. The rest is the same as Example 1.
[0093] Example 3
[0094] The only difference between Example 3 and Example 1 is that in step (1) of the preparation method, the mass fraction of the aluminum oxide powder is 95.8%, and the mass fraction of the zirconium oxide powder is 0.2%. The rest is the same as Example 1.
[0095] Example 4
[0096] The only difference between Example 4 and Example 1 is that in step (3) of the preparation method, in the suspension, the mass fraction of ZTA powder is 12%, and the mass fraction of alumina powder is 88%. The rest is the same as Example 1.
[0097] Example 5
[0098] The only difference between Example 5 and Example 1 is that in step (3) of the preparation method, in the suspension, the mass fraction of ZTA powder is 25%, and the mass fraction of alumina powder is 75%. The rest is the same as Example 1.
[0099] Example 6
[0100] The only difference between Example 6 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 3 μm, and in step (3), the particle size of the alumina powder is 0.15 μm. The rest is the same as Example 1.
[0101] Example 7
[0102] The only difference between Example 7 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 8 μm, and in step (3), the particle size of the alumina powder is 0.15 μm. The rest is the same as Example 1.
[0103] Example 8
[0104] The only difference between Example 8 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 3 μm, and in step (3), the particle size of the alumina powder is 0.5 μm. The rest is the same as Example 1.
[0105] Example 9
[0106] The only difference between Example 9 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 8 μm, and in step (3), the particle size of the alumina powder is 0.5 μm. The rest is the same as in Example 1.
[0107] Example 10
[0108] The only difference between Example 10 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 5 μm, and in step (3), the particle size of the alumina powder is 0.2 μm. The rest is the same as Example 1.
[0109] Embodiment 11
[0110] The only difference between Example 11 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 5.7 μm, and in step (3), the particle size of the alumina powder is 0.4 μm. The rest is the same as in Example 1.
[0111] Example 12
[0112] The only difference between Example 12 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 8 μm, and in step (3), the particle size of the alumina powder is 0.4 μm. The rest is the same as Example 1.
[0113] Example 13
[0114] The only difference between Example 13 and Example 1 is that in step (4) of the preparation method, the ratio of the thickness of the surface layer of the composite material to the ZTA substrate green body is 1:20, and the rest is the same as Example 1.
[0115] Embodiment 14
[0116] The only difference between Example 14 and Example 1 is that in step (4) of the preparation method, the ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA matrix green body is 1:500, and the rest is the same as Example 1.
[0117] Comparative Example 1
[0118] Comparative Example 1 is a traditional ZTA substrate prepared, that is, Comparative Example 1 only contains a ZTA substrate and does not contain a composite material surface layer. Compared with Example 2, its preparation method only contains steps (1), (2) and (5).
[0119] Comparative Example 2
[0120] Comparative Example 2 is a traditional ZTA substrate prepared, that is, Comparative Example 2 only contains a ZTA substrate and does not contain a composite material surface layer. Compared with Example 3, its preparation method only contains steps (1), (2) and (5).
[0121] Comparative Example 3
[0122] The only difference between Comparative Example 3 and Example 1 is that in step (3) of the preparation method, in the suspension, the mass fraction of ZTA powder is 10%, and the mass fraction of alumina powder is 90%. The rest is the same as Example 1.
[0123] Comparative Example 4
[0124] The only difference between Comparative Example 4 and Example 1 is that in step (3) of the preparation method, in the suspension, the mass fraction of ZTA powder is 30%, and the mass fraction of alumina powder is 70%. The rest is the same as Example 1.
[0125] Comparative Example 5
[0126] The only difference between Example 5 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 2.5 μm, and in step (3), the particle size of the alumina powder is 1 μm. The rest is the same as in Example 1.
[0127] Comparative Example 6
[0128] The only difference between Example 6 and Example 1 is that in step (1) of the preparation method, the particle size of the ZTA powder is 8.5 μm, and in step (3), the particle size of the alumina powder is 0.1 μm. The rest is the same as in Example 1.
[0129] Comparative Example 7
[0130] The only difference between Comparative Example 7 and Example 1 is that in step (4) of the preparation method, the ratio of the thickness of the surface layer of the composite material to the ZTA substrate green body is 1:19, and the rest is the same as Example 1.
[0131] Comparative Example 8
[0132] The only difference between Comparative Example 8 and Example 1 is that in step (4) of the preparation method, the ratio of the thickness of the surface layer of the composite material to the ZTA substrate green body is 1:510, and the rest is the same as Example 1.
[0133] The relevant parameters in the above-mentioned Examples 1-14 and Comparative Examples 1-8 are shown in Table 1.
[0134] Table 1: Related parameters in Examples 1-14 and Comparative Examples 1-8
[0135]
[0136]
[0137] Performance Testing
[0138] 1. Thermal conductivity / bending strength / thermal expansion coefficient test
[0139] The products prepared in Examples 1-14 and Comparative Examples 1-8 were tested for thermal conductivity / bending strength / thermal expansion coefficient, wherein the test methods and standards are shown in Table 2, and the test results are shown in Table 3.
[0140] Table 2: Test items, methods and standards
[0141]
[0142] Table 3: Test results of Examples 1-14 and Comparative Examples 1-8
[0143]
[0144]
[0145] It can be seen from Table 3 that the composite ZTA substrates of Examples 1-14 have high thermal conductivity, good bending strength and small thermal expansion coefficient as a whole.
[0146] Specifically, in Example 1, the ZTA powder ratio, suspension ratio, particle size range and composite material surface thickness all fall within the specified preferred range, with high thermal conductivity, good bending strength and small thermal expansion coefficient.
[0147] In Examples 2-3, the ratio of alumina powder to zirconia powder in the preparation of ZTA powder is taken at the end point, and the performance is qualified. However, when the content of zirconia powder in Example 2 is relatively large, the sintering temperature of ZTA powder is relatively low, the thermal expansion coefficient of the obtained ZTA ceramic is relatively large, and the thermal conductivity is relatively small; when the content of zirconia powder in Example 3 is relatively small, the sintering temperature of ZTA powder is relatively high, and the thermal expansion coefficient of the obtained ZTA ceramic is smaller than that of Example 2, and the thermal conductivity is greater than that of Example 2.
[0148] In Examples 4-5, the ratio of alumina powder to ZTA powder is taken at the endpoint when the suspension is prepared. When the ZTA content in the suspension is small, the toughness of the ZTA ceramic matrix is poor, resulting in a small bending strength of the ceramic after sintering.
[0149] In Examples 6-12, when the particle size of the ZTA powder is small, the particle sizes of the two are not much different, the alumina powder is coated on the surface of the ZTA powder to form pores, the uniformity of the formed composite network structure is general, and the bonding strength and bending strength performance of the composite substrate are slightly improved; when the particle size ratio of ZTA to alumina is large, that is, the particle size of the ZTA powder is large, the particle size of alumina is too fine, affecting its dispersibility, and a large number of grain boundaries are formed, resulting in little improvement in thermal conductivity.
[0150] In Examples 13-14, the thickness ratio of the composite material surface layer and the ZTA substrate layer is taken at the endpoints. When the thickness ratio is larger, the ZTA layer is thicker and the composite material surface layer is thinner. The content of the composite material accounts for a relatively low proportion of the overall content of the composite ZTA substrate, and the thermal conductivity value is not greatly improved. When the thickness ratio is smaller, the thickness of the ZTA substrate is relatively thin, and the bending strength performance of the sintered substrate is average.
[0151] Comparative Example 1-2 is a traditional ZTA formula. In this case, the ZTA substrate has no composite surface structure and cannot take advantage of the high thermal conductivity of the composite surface. As a result, the thermal conductivity, bending strength and thermal expansion coefficient of the prepared composite substrate are poor.
[0152] In comparative example 3-4, the ratio of ZTA powder to alumina powder in the suspension preparation is not within the ratio range of the present invention, so that the thermal conductivity and thermal expansion coefficient are unqualified, and when the ZTA powder content is too small, the bending strength of the ZTA substrate is affected.
[0153] In Comparative Examples 5-6, the particle size of the ZTA powder and the particle size of the alumina powder in the suspension are not within the particle size range of the present invention, and the thermal conductivity and thermal expansion coefficient are unqualified. When the particle size of the ZTA powder is too small, that is, when it is not much different from the particle size of the alumina powder, it cannot be well coated by alumina, and the formed composite network structure is missing, which affects its thermal conductivity; when the particle size of the alumina powder is too small, the electrostatic force between the powders is strong, and the powders are easy to agglomerate, and the finer the powder, the more grain boundaries are formed, which will enhance the intensity of phonon scattering by the grain boundaries, resulting in reduced thermal conductivity of the material. When the particle size of the ZTA powder is too large, the porcelain strength after sintering is low, and the accumulation of local particles of the material causes differences in densification, making the pore structure coarser after sintering, affecting strength and thermal conductivity.
[0154] In Comparative Examples 7-8, the ratio of the thickness of the composite surface layer to the ZTA substrate is not within the scope of the present invention, and the thermal conductivity or flexural strength performance is unqualified. When the ratio of the thickness of the composite surface layer to the ZTA substrate is less than 1:500, the ZTA substrate thickness is too thick, the composite surface layer is too thin, the content of the composite material accounts for a relatively low proportion of the overall content of the composite ZTA substrate, and the thermal conductivity is reduced. When the ratio of the thickness of the composite surface layer to the thickness of the ZTA substrate is greater than 1:20, the thickness of the ZTA substrate is too thin, and the flexural strength of the product is reduced.
[0155] 2.XRD test
[0156] XRD tests were performed on the composite material layers in the composite ZTA substrates prepared in Examples 1-3 and 10 and the ZTA substrate prepared in Comparative Example 1-2 to observe the peak intensities of the
[006] and
[110] planes of alumina. The test results are shown in Table 4.
[0157] Table 4: Peak intensities of the
[006] and
[110] planes of aluminum oxide
[0158]
[0159]
[0160] It can be seen from Table 4 that the peak intensity ratio of the
[006] plane to the
[110] plane of aluminum oxide in the composite material layer of the present invention is 10%-45%; the peak intensity ratio of the
[006] plane to the
[110] plane of aluminum oxide in the ZTA substrate of Comparative Example 1 is 9.87%, which is less than 10%; the peak intensity ratio of the
[006] plane to the
[110] plane of aluminum oxide in the ZTA substrate of Comparative Example 2 is 46.03%, which is greater than 45%. The peak intensity data of the
[006] plane to the
[110] plane of aluminum oxide in Comparative Examples 1 and 2 are consistent with the performance effect data of Comparative Examples 1 and 2. Because when I 006 / I 110 When the ratio is lower than 10%, the anti-seismic performance is poor, the crystal grows in a directional manner during sintering, the arrangement structure is tight, the thermal expansion coefficient is high, and the overall performance is poor. If the ratio is higher than 45%, the atomic arrangement of the
[006] crystal plane and the
[110] crystal plane in the alumina crystal is different, the growth is anisotropic, resulting in different surface driving energy, large differences in the growing grain boundaries, and poor bending strength and thermal conductivity of the sintered substrate.
[0161] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite ZTA substrate, characterized in that: It includes a ZTA substrate and a composite material surface layer located on the ZTA substrate; the composite material surface layer includes aluminum oxide and ZTA; and the aluminum oxide is coated around the ZTA to form a wrapping structure; The ratio of the thickness of the surface layer of the composite material to the thickness of the ZTA substrate is 1:(20-500); In the surface layer of the composite material, the mass percentage of the aluminum oxide is 75-88%, and the mass percentage of the ZTA is 12-25%; In the surface layer of the composite material, the XRD diffraction peak intensity of the aluminum oxide [006] plane is 10-45% of the XRD diffraction peak intensity of the aluminum oxide [110] plane.
2. The composite ZTA substrate according to claim 1, characterized in that: The raw materials for preparing the ZTA include alumina powder, zirconium oxide powder and a sintering aid.
3. The composite ZTA substrate according to claim 2, characterized in that: The mass percentage of the aluminum oxide powder is 91.2-95.8%, the mass percentage of the zirconium oxide powder is 0.2-4.8%, and the rest is sintering aid.
4. The composite ZTA substrate according to claim 3, characterized in that: The sintering aid includes at least one of Y2O3, MgO, CaO, SiO2, TiO2, CeO2, Cr2O3, La2O5, BaO, SrO, Sc2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3 and Ho2O3.
5. The method for preparing the composite ZTA substrate according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing alumina powder, zirconium oxide powder and a sintering aid, crushing and granulating to obtain ZTA powder; (2) mixing the ZTA powder obtained in step (1) with an organic solvent and a first auxiliary agent, performing tape casting, drying, and pre-sintering to remove binder to obtain a ZTA substrate green body; (3) mixing the ZTA powder obtained in step (1) with water, a second auxiliary agent, and alumina powder to obtain a suspension; (4) spraying the suspension obtained in step (3) onto the ZTA substrate green body obtained in step (2), and drying to obtain a composite ZTA substrate green body; (5) sintering the composite ZTA substrate green body obtained in step (4) to obtain a composite ZTA substrate; The ratio of the particle size of the ZTA powder to the particle size of the alumina powder is (0.6-1.6):(0.03-0.1); the second auxiliary agent includes a dispersant and a defoaming agent.
6. The preparation method according to claim 5, characterized in that: In step (2), the organic solvent includes at least one of butyl acetate, ethyl acetate and anhydrous ethanol; and the first auxiliary agent includes a dispersant, a binder, a plasticizer and a defoaming agent.
7. The preparation method according to claim 5, characterized in that: In step (5), the sintering temperature is 1200-1500° C. and the sintering holding time is 20-70 min.
8. An electronic product, characterized in that: A composite ZTA substrate comprising any one of claims 1 to 4.
Citation Information
Patent Citations
Aluminum oxide reinforced ZTA ceramic substrate and preparation method thereof
CN112645696A
Zirconium oxide toughened aluminum oxide ceramic plate and preparation method thereof
CN113292323A